EVALUASI DAYA TAMPUNG TERHADAP BEBAN PENCEMAR MENGGUNAKAN MODEL KUALITAS AIR (STUDI KASUS: SUNGAI WINONGO) - Nelly Marlina; Kasam Kasam; Any Juliani (Asian Journal of Innovation and Entrepreneurship, 2015)
The increasing of human’s activities caused the pollution load going up. It affected the amount of the Winongo River’s capacity. One of the river management attempts was find out the amount of the capacity with a modeling method. The modeling program in this research was Qual2Kw. The research method was supported by the secondary and primary data treated by the Qual2Kw program. This research was divided in three scenarios. The trial results showed that the BOD concentration in the along of the river was 16 mg/L, the DO concentration was 2.4 mg/L, 7 of pH, and 26oC of temperature. The condition of BOD from the upstream to the downstream in the existing condition had exceeded the quality standards, 3 mg/L. The attempts to decrease the pollution load capacity of Winongo River by 2012 was decreasing the pollution load from the point source 959.25 kg/day and from the diffuser source was 193.75 kg/day. The another effort was making the IPAL Komunal in each sub-districts. Keywords: Winongo River, capacity, Qual2Kw